The Impact of Uzbekistan’s Accession to the World Trade Organization on National Economic Security - Bobomurodova Mahliyo Rustam qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article provides a comprehensive analysis of the impact of Uzbekistan’s accession to the World Trade Organization (WTO) on national economic security. It examines the economic benefits and risks of joining the WTO, as well as key aspects of national economic security, including macroeconomic stability, trade diversification, foreign investment, energy security, and food security. The analysis focuses on strategies to ensure national economic security within the context of Uzbekistan’s economic reforms and integration into the global trade system.